The Energy Performance Evaluation of Buildings in an Evolving Built Environment: An Operative Methodology. (June 2016) - Sala, Mariaemma; López, Cristina S. Polo; Frontini, Francesco; Tagliabue, Lavinia Ch.; De Angelis, Enrico
Abstract: The paper is based on a case study in Switzerland, where the Cantonal Director Plan, expected for the next years, will change the urban density. The plan allows raising from three and four floors the height of the existing buildings now separated by streets that are quite narrow, to get over up to eight floors, without modifying the width of street. A case study located in Paradiso municipality, part of Lugano's city (CH) is used to understand and quantify the impact of the future buildings on the energy performance of historical heritage buildings. The building adopted as case study is protected as cultural monument by the new Master Plan and listed in the sectorial regulations for the landscape. However, this building as others in the area is strongly influenced by the new changes in act, due to the New Master Plan, in term of solar availability and thus energy demand. The actual urban density scenario is compared to the future one to evaluate through dynamic energy simulation the change affecting the building considering the energy and economic aspects.